Analisis Potensi Jalur Manifestasi Panas Bumi Maronge Kabupaten Sumbawa Menggunakan Data Gayaberat GGMPlus - Muwardi Sutasoma; Rosita Wijayanti; Adi Susilo; Mohammad Habibiy Idmi; Neila Ayuzita Azhalia; Meidi Arisalwadi (Program Studi Fisika - Universitas San Pedro, 2026)
The increasing national energy demand necessitates the utilization of renewable resources, particularly geothermal energy, which holds significant potential in Indonesia. This research aims to identify potential geothermal manifestation pathways in the Maronge area, Sumbawa (NTB), characterized by surface features (hot springs, fumaroles) with temperatures ranging from 35-43°C. The methodology employed is the gravity method based on GGMPlus satellite data to map subsurface rock density variations. The gravity data processing includes calculating the Complete Bouguer Anomaly (CBA), separating the CBA into regional and residual anomalies using the upward continuation filter, and conducting further analysis using the First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) technique. The results indicate a negative anomaly in the central area of the study, which is strongly suspected to signify a fault zone or low-density hydrothermal alteration zone. This contact zone serves as a conduit for hot fluids, explaining the emergence of the surface manifestations as an upflow zone. The results of this study can provide additional information for the government in formulating policies for managing the Maronge hot spring potential.